Rotary Wing Aerodynamics - Zanotti, Alex (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book contains state-of-the-art experimental and numerical studies showing the most recent advancements in the field of rotary wing aerodynamics and aeroelasticity, with particular application to the rotorcraft and wind energy research fields.